On imitative and creative art of parabiblical texts’ author. Remarks on biblical quotations in the second Slavic translation of the Palaea historica - Skowronek, Małgorzata (Studia Ceranea, 2016)
The aim of the paper is to present the results of analysis of the biblical quotations and borrowings found in the Palaea Historica (9th century) in its second Slavic translation, according mostly to the classification of biblical quotations given by M. Garzaniti (2014). Having its narrative material based on the Octateuch as well as the Books of Samuel, Books of Kings and Books of Chronicles, the Palaea contains a variety of adaptations of the biblical text, which provide evidence for the creative usage of the hypertext (through inter al. summary, contamination of episodes, expansion of details, dramaturgization). Literal quotations from the Old and New Testaments also form an important group of such borrowings. Curiously, a part of these play no narrative role, but rather a structural one, as they summarize the meanings of particular chapters (stories).